Asuhan Keperawatan Nyeri Akut Pada Ny. S Dengan Post Sectio Caesarea Ketuban Pecah Dini (KPD) Melalui Penerapan Aromaterapi Bitter Orange Di Ruang Sebetul RSAL dr. Midiyato Suratani Tanjungpinang Tahun 2025 - Fadhilah Mufarrichah; Meily Nirnasari; Komala Sari (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Caesarean section delivery (cesarean section) has several potential problems, both for the mother and the baby. Some common problems in the mother include bleeding, wound infection, urinary tract problems, blood clots, and pain. In infants, risks include respiratory disorders and wounds due to incisions. The purpose of this scientific paper is to provide comprehensive nursing care to patients with acute pain through the application of bitter orange aromatherapy. This research was conducted in the Sebetul room of RSAL dr. Midiyato Suratani Tanjungpinang from 28-30 October 2024 starting from the assessment, data analysis, diagnosis, intervention, implementation, and evaluation stages. The design of this research is in the form of a case study involving 1 respondent, namely Mrs. S. The results of nursing care showed a decrease in the pain scale using a numeric pain scale (Numeric Rating Scale). Before the action was taken, the pain scale was 7 and after the action, the pain scale became 2. It is hoped that the results of this scientific paper can be used as information and reference material for health services in reducing pain in patients through the application of bitter orange aromatherapy as an alternative pain management in patients.